Kinerja Pertumbuhan Sapi Bali Jantan Yang Diberikan Pakan Komplit Berbahan Dasar Pakan Pola Peternak dan Silase Campuran Rumput Kume(Shorgum Plumosum Var. Timorense)- Legum Clitoria Tarnatea Dengan Imbangan Yang Berbeda: Growth Performance Of Male Bali Cattle Provided Complete Feed Based On Farming Pattern Feed And Mixed Silage Grass Kume (Shorgum plumosum var. Timorense)-Legum Clitoria tarnatea With A Different Balance - Oelbata, Winger; Kihe, Johny Nada; Maranatha, Grace (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of providing complete feed based on local feed by farmers pattern westTimor and silage mixture of kume grass (Shorgum plumosum var. Timorense)-legume Clitoria tarnatea withdifferent proportions on increase in chest circumference, body length and shoulder heightof fattening male Balicattle. This study used 4 male Bali cattle aged 1-1.5 years in the body weight range of 110-115 kg with anaverage of 112.88 kg and a coefficient variation of 4.22%. The method used is an experimental method usingthe Latin Square Design (LSD) with 4 treatments and 4 periods as replications. The treatments in this studywere P0 ; local feed by farmers pattern west Timor (Control), P1 ; local feed by farmers pattern west Timor60%+grass-legume silage 30%+concentrate 10%, P2 ; local feed by farmers pattern west Timor 50%+grass-legume silage 40%+concentrate 10%, P3 ; local feed by farmers pattern west Timor 40% + grass-legume silage50% + 10% concentrate. The data obtained were analyzed using Analysis of variance (ANOVA). The results ofthe study, the average daily increase in chest circumference (cm/e/h) P0;0.13±0.022,P1; 0.14±0.005,P2;0.15±0.029,P3; 0.14±0.021, daily body length gain(cm/e/h)P0;0.09±0.010,P1;0.10±0.021,P2;0.12±0.022,P3;0.12±0.017 anddaily increase in shoulderheight(cm/e/h) P0;0.08±0.021,P1; 0.11±0.017,P2;0.13±0.018,P3; 0.10±0.016. The results of statistical analysisshowed that the treatment had a significant effect of p<0.05 on increase in chest circumference, body length andshoulder height of fattening male Bali cattle. The conclusion of this study is that the provision of complete feedbased on local feed by farmers pattern west Timor and silage mixture of grass-legume with different proportionshas an effect on increasing daily weight gain of fattening bali cattle compared to control treatment, while theparameters of increase in chest circumference, body length and shoulder height did not show any effect betweentreatments Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pakan komplit berbahan dasar pakan polapeternak dan silase campuran rumput kume (Shorgum plumosum var. Timorense)-legum Clitoria tarnateadengan imbangan yang berbeda terhadap pertambahan lingkar dada, panjang badan dan tinggi pundak sapi Balijantan penggemukan. Penelitian ini menggunakan 4 ekor sapi Bali jantan berumur 1-1,5 tahun pada kisaranberat badan 110-115 kg dengan rataan 112,88 kg dan koefisien variasi 4,22%. Metode yang digunakan adalahmetode percobaan menggunakan Rancangan Bujur Sangkar Latin (RBSL) dengan 4 perlakuan dan 4 periodesebagai ulangan. Adapun perlakuan dalam penelitian ini adalah P0 ; Pakan pola peternak (Kontrol), P1 ; Pakanpola peternak 60%+silase rumput-legum 30%+konsentrat 10%, P2 ; Pakan pola peternak 50%+silase rumput-legum 40%+konsentrat 10%, P3 ; Pakan pola peternak 40%+silase rumput-legum 50%+konsentrat 10%. Datayang diperoleh dianalisis menggunakan Analisis of variance (ANOVA). Dari hasil penelitian diperoleh rataanpertambahan lingkar dada harian (cm/e/h) P0;0.13±0.022,P1; 0.14±0.005, P2;0.15±0.029,P3; 0.14±0.021,pertambahan panjang badan harian(cm/e/h)P0;0.09±0.010,P1;0.10±0.021,P2;0.12±0.022,P3;0.12±0.017 danpertambahan tinggi pundak harian(cm/e/h) P0;0.08±0.021,P1; 0.11±0.017,P2;0.13±0.018,P3; 0.10±0.016. Hasilanalisis statistik menunjukkan bahwa perlakuan berpengaruh tidak nyata p>0,05 terhadappertambahan lingkardada, panjang badan dan tinggi pundak sapi Bali jantan penggemukan. Kesimpulan dari penelitian ini yaitu,pemberian pakan komplit berbahan dasar pakan pola peternak dan silase campuran rumput kume-legumClitoriatarnateadengan imbangan yang berbeda, tidak memberikan pengaruh antar perlakuan terhadap pertambahanlingkar dada, panjang badan dan tinggi pundak.